APLIKASI PENGELOLAAN LAUNDRY MENGGUNAKAN VISUAL BASIC - Naugis Sahmadani; Haria Nansa Rahmadhany; Rizky Basatha (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
In today's digital era, the laundry business faces challenges in improving transaction efficiency to remain competitive. Customers often struggle to track the status of their laundry and obtain accurate information regarding completion times. To address these issues, a laundry system application based on VB.NET has been developed using the Visual Studio platform. This application is designed for order management, laundry returns, and payment transactions, thereby reducing the potential for human error and increasing operational efficiency. Additionally, the application offers real-time laundry status tracking, enabling customers to monitor the progress of their orders. The integrated system between customers and service providers also enhances interaction and communication more efficiently. By using the VB.NET programming language and the Visual Studio platform, this application is expected to become an innovative solution that meets customer needs and helps laundry service providers improve productivity and competitiveness in an increasingly competitive market.